Hubungan Penguasaan Kosakata dan Tata Bahasa Indonesia dengan Kemampuan Menulis Teks Naratif Siswa Kelas VII Sekolah Menengah Pertama Negeri 5 Kota Serang - Hanny Maulida Mawaddah; Sobri Sobri; Ade Anggraini Kartika Devi (Jurnal Bahastra, 2026)
This study addresses the persistent challenges faced by junior secondary school students in producing coherent narrative texts, which are closely associated with their mastery of vocabulary and grammatical competence in Indonesian. The research investigates the extent to which vocabulary mastery and Indonesian grammar proficiency are related to students’ narrative writing ability among seventh-grade students at SMP Negeri 5 Kota Serang. Employing a correlational research design, the study utilizes descriptive statistical analysis, prerequisite testing, and hypothesis testing to examine the relationships among variables. The findings reveal significant positive correlations between vocabulary mastery and narrative writing ability (r = 0.587 > 0.242), as well as between grammar mastery and narrative writing ability (r = 0.661 > 0.242). Furthermore, the combined contribution of vocabulary and grammar mastery to students’ narrative writing ability is substantial, with a coefficient of determination of 0.537, indicating that both variables jointly explain a considerable proportion of variance in writing performance. These results demonstrate that linguistic competence, particularly in vocabulary and grammar, plays a critical role in shaping students’ ability to construct effective narrative texts, reinforcing the argument that integrated language instruction is essential for improving writing outcomes.